A protective role for type I interferon signaling following infection with Mycobacterium tuberculosis carrying the rifampicin drug resistance-conferring RpoB mutation H445Y. - Suhas Bobba; Kuldeep S Chauhan; Sadia Akter; Shibali Das; Ekansh Mittal; Barun Mathema; Jennifer A Philips; Shabaana A Khader (PLoS Pathogens)
Interleukin-1 (IL-1) signaling is essential for controlling virulent Mycobacterium tuberculosis (Mtb) infection since antagonism of this pathway leads to exacerbated pathology and increased susceptibility. In contrast, the triggering of type I interferon (IFN) signaling is associated with the progression of tuberculosis (TB) disease and linked with negative regulation of IL-1 signaling. However, mice lacking IL-1 signaling can control Mtb infection if infected with an Mtb strain carrying the rifampin-resistance conferring mutation H445Y in its RNA polymerase β subunit (rpoB-H445Y Mtb). The mechanisms that govern protection in the absence of IL-1 signaling during rpoB-H445Y Mtb infection are unknown. In this study, we show that in the absence of IL-1 signaling, type I IFN signaling controls rpoB-H445Y Mtb replication, lung pathology, and excessive myeloid cell infiltration. Additionally, type I IFN is produced predominantly by monocytes and recruited macrophages and acts on LysM-expressing cells to drive protection through nitric oxide (NO) production to restrict intracellular rpoB-H445Y Mtb. These findings reveal an unexpected protective role for type I IFN signaling in compensating for deficiencies in IL-1 pathways during rpoB-H445Y Mtb infection.